A Mixed TEHL Model for the Prediction of Thermal Effect on Lubrication Performance in Spiral Bevel Gears. Issue 2 (3rd March 2020) - Wang, Daofei; Ren, Si; Zhang, Ying; Pu, Wei
Abstract: Arbitrary velocity vectors on two meshing surfaces in spiral bevel gears could generate large sliding velocity, which may cause a tremendous temperature rise, especially when surface roughness is involved. However, available studies are primarily concentrated on full-film lubrication without considering temperature rise and surface topography. The purpose of present study is to develop a mixed thermal elastohydrodynamic lubrication (TEHL) model taking into account the velocity vector and surface roughness. The obtained results are compared with those from an elastohydrodynamic lubrication (EHL) model and measurements in previous literature to demonstrate the accuracy of the present model. Further, the TEHL model has been applied to predict the film thickness, pressure, and temperature rise of spiral bevel gears over one meshing period by considering thermal effects.